Prenatal Valproate Exposure Differentially Affects Parvalbumin-Expressing Neurons and Related Circuits in the Cortex and Striatum of Mice - Lauber, Emanuel; Filice, Federica; Schwaller, Beat (Frontiers in Molecular Neuroscience, 2016)
Autism spectrum disorders (ASD) comprise a number of heterogeneous neurodevelopmental diseases characterized by core behavioral symptoms in the domains of social interaction, language/communication and repetitive or stereotyped patterns of behavior. In utero exposure to valproic acid (VPA) has evolved as a highly recognized rodent ASD model due to the robust behavioral phenotype observed in the offspring and the proven construct-, face- and predictive validity of the model. The number of parvalbumin-immunoreactive (PV+) GABAergic interneurons has been consistently reported to be decreased in human ASD subjects and in ASD animal models. The presumed loss of this neuron subpopulation hereafter termed Pvalb neurons and/or PV deficits were proposed to result in an excitation/inhibition imbalance often observed in ASD. Importantly, loss of Pvalb neurons and decreased/absent PV protein levels have two fundamentally different consequences. Thus, Pvalb neurons were investigated in in utero VPA-exposed male (“VPA”) mice in the striatum, medial prefrontal cortex (mPFC) and somatosensory cortex (SSC), three ASD-associated brain regions. Unbiased stereology of PV+ neurons and Vicia Villosa Agglutinin-positive (VVA+) perineuronal nets (PNNs), which specifically enwrap Pvalb neurons, was carried out. Analyses of PV protein expression and mRNA levels for Pvalb, Gad67, Kcnc1, Kcnc2, Kcns3, Hcn1, Hcn2 and Hcn4 were performed. We found a ~15% reduction in the number of PV+ cells and decreased Pvalb mRNA and PV protein levels in the striatum of VPA mice compared to controls, while the number of VVA+ cells was unchanged, indicating that Pvalb neurons were affected at the level of the transcriptome. In selected cortical regions (mPFC, SSC) of VPA mice, no quantitative loss/decrease of PV+ cells was observed. However, expression of Kcnc1, coding for the voltage-gated potassium channel Kv3.1 specifically expressed in Pvalb neurons, was decreased by ~40% in forebrain lysates of VPA mice. Moreover, hyperpolarization-activated cyclic nucleotide-gated channel (HCN) 1 expression was increased by ~40% in the same samples from VPA mice. We conclude that VPA leads to alterations that are brain region- and gene-specific including Pvalb, Kcnc1 and Hcn1 possibly linked to homeostatic mechanisms. Striatal PV down-regulation appears as a common feature in a subset of genetic (Shank3B-/-) and environmental ASD models.